Holocene vegetation history of Banks Island, Northwest Territories, Canada - Gajewski, K; Mott, R J; Ritchie, J C; Hadden, K (Canadian Journal of Botany, 2000)
Four pollen diagrams from Banks Island, Northwest Territories, provide the first records of the postglacial vegetation of the region. Chronologies are estimated from radiocarbon dates and by correlation of the exotic-pollen curves to data from the mainland. The pollen stratigraphies from all sites can be divided into three zones, where the middle zone, dating from 7000 to 2000 BP, corresponds to the warmest time. Although both the first and third zones correspond to cooler periods, the vegetation of the earliest zone was not identical to that of the latest, indicated by lower frequencies of key pollen types such as those of Dryas and Saxifraga.Key words: Banks Island, Holocene, pollen diagram, Arctic, paleoecology, Quaternary.